Spatial Disparities in Jakarta’s Health and Education Infrastructures: An OpenStreetMap-Based Analysis - Ramadhanis, Zainab; Akrimullah, Anjar; Heriza, Dewinta (Jurnal Teknik Sipil dan Lingkungan, 2025)
Jakarta, as Indonesia’s most populous megacity, had a population of 11.14 million in 2024. Covering an area of 661 square kilometers, it is also the country’s most densely populated city, with over 16,500 individuals per square kilometer. High population density brings challenges, particularly in access to essential public services like education and healthcare, which are crucial for sustainable urban development. This study examines spatial disparities in the distribution of health and educational infrastructures in Jakarta concerning population density. Through overlay analysis, two models were developed: the Educational Facilities Gaps Map and the Health Facilities Gaps Map, categorizing areas as well-served, moderately served, or underserved. The findings highlight significant disparities across Jakarta’s administrative regions. Central Jakarta has the highest accessibility, with 57.43% of its area well-served for education and 65.06% for healthcare. Conversely, North Jakarta and Kepulauan Seribu experience the most severe service gaps, with 51.92% and 100% of their areas underserved in education, and 50.20% and 85.92% in healthcare, respectively. East, South, and West Jakarta exhibit moderate service coverage, though underserved zones remain. These results emphasize the importance of strategic urban planning to improve equitable access to public services. By incorporating geospatial analysis into policymaking, decision-makers can optimize facility distribution and infrastructure development, reducing service disparities, especially in underserved areas.